Doença de Kawasaki com sintomas iniciais atípicos: um relato de caso - Tami Guerreiro Estevam Vieira; Bárbara Silva Ton; Marcella Calazans Reblin de Oliveira; Gabriela de Lima Carlesso; Sara Costa Silva (Sociedade Brasileira de Pediatria, 2024)
INTRODUCTION: Kawasaki disease (KD) is an acute, self-limited, systemic vasculitis of unknown etiology. The diagnosis is essentially clinical and the treatment is based on the use of intravenous human immunoglobulin (IVIG) and acetylsalicylic acid (ASA) in anti-inflammatory dose, being ideally initiated by the tenth day of the onset of symptoms in order to avoid the complications associated with this pathology. METODOLOGY: This is a case report of a 9-year-old child with Kawasaki syndrome with atypical initial presentation. DISCUSSION: Previously healthy child, presenting febrile jaundice hemorrhagic syndrome and influenza syndrome, associated with radiological changes that could be correlated with SARS-COV-2 infection, without initially ruling out the hypothesis of Pediatric Multisystemic Inflammatory Syndrome (SIM-P). After negative serologies and cultures, there was a progressive remission of symptoms, except for the fever. Criteria for KD were met on the 16th day of evolution, when monotherapy with ASA without IVIG was initiated, with resolution of the fever. CONCLUSION: It is essential to be aware of the possible variations in the clinical presentation of KD and correlate it with the epidemiological and social context of the patient, due to the morbidity related to this vasculitis.